Effect of Stream River and Tidal on the Suspended Sediment Concentration of Kuala Langsa Estuary, Aceh, Indonesia - Irwansyah Irwansyah; Faiz Isma; Yulina Ismida; Muhammad Fauzan Isma; Suliadi Firdaus Sufahani; Helmy Akbar (Marine Science Department Diponegoro University, 2023)
Kuala Langsa estuary is a semi-closed zone where there is an exchange of two water masses between river and tidal of the Malacca Strait. The exchange of those two water masses occurs as a physical result of fluctuating estuaries. This caused Suspended Sediment Concentration (SSC) continue to increase as the estuary is the final distribution point for sediment brought from upstream by erosion in the Langsa River. This sediment contributes to the silting of Langsa estuary. This is caused the KRI dr. Soeharso Hospital to be unable to dock at the Kuala Langsa Port during the 66th Surya Bhaskara Jaya Navy Operations 2017. It’s necessary to study estuary physical conditions, which include bathymetry, currents, temperature, salinity, and concentrations of floating sediment that occur as a result of the tides and river discharges. This research used quantitative and qualitative exploratory methods, analyzed a direct correlation between the measurement results, roughness coeficient, and sediment transport rate used relevant empirical equations (Duboy's, Einstein's, Rottner, Chang, Simons, and Richardson, and Lane and Kalinske aquations). This research found that the Langsa estuary is 16 km with a semidiurnal tidal type. In the Langsa estuary, it was discovered that the highest sediment rate was at the mouth of the estuary is 10.700.739,71 ton/day-1 and the physical model of Muara Langsa has a good correlation to the results of measurements-model indicate value of CC width = 0.959 and tide CC= 0.421, This study provides initial information for conducting hydrodynamic and morphological models at the mouth of estuary.